Debunking disinformation on YouTube: a fact check on the 2024 Indonesian election - Alamsyah, Purnama; Hakim, Lukman Nul; Wijaya, Gustaf; Wicaksono, Arditya (Jurnal Studi Komunikasi, 2024)
The increasing number of hoaxes circulating on digital platforms in Indonesia is concerning. Following the 2024 Indonesian presidential election, the spread of disinformation, specifically on YouTube, has intensified, posing significant risks to public trust and the electoral process. These hoaxes have the potential to destabilise societal harmony and influence voter perceptions. In response, fact-checker institutions have played a critical role in exposing disinformation. This article explores the mechanisms of assessing accuracy on YouTube during the 2024 election, focusing on how Indonesian fact-checking institutions operate. The research used a qualitative approach, with two data collection techniquesâ€“ interviews with key stakeholders and field observations of fact-checking processes. This research revealed that fact-checking in Indonesia is falling behind the rapid disinformation production. Combating disinformation requires more than current effortsâ€”it demands a coordinated, resource-intensive approach involving the executive, legislative, judiciary, and civil society’s active engagement. Innovative policies, technological advancements, and well-trained human resources are imperative to ensure its effectiveness.